Acute Disseminated Encephalomyelitis in Children: A Single Institution Experience of 28 Patients - Hung, Po-Cheng; Wang, Huei-Shyong; Chou, Ming-Liang; Lin, Kuang-Lin; Hsieh, Meng-Ying; Wong, Alex M-C (Neuropediatrics, 2012)
The aim of this study is to describe the clinical, laboratory, and neuroimaging features, treatment and outcome of acute disseminated encephalomyelitis (ADEM) in Taiwanese children to compare with two series from United States of America and Japan. We retrospectively reviewed the medical records and magnetic resonance images of 28 children, 23 boys and 5 girls, with ADEM between January 2001 and December 2009. Their mean age at disease onset was 6 years 9 months. Twenty four children experienced a prodromal illness. There was no special seasonal distribution in our patients. They presented mostly with impaired consciousness and headache. Cerebrospinal fluid samples of 21 patients were analyzed and none showed intrathecal oligoclonal bands. Magnetic resonance imaging showed variable findings: lesions with abnormal signal changes frequently found in the subcortical white matter of frontal and parietal lobes. No patient showed cortical gray matter involvement. We also found a high rate of deep gray matter involvement including thalami and basal ganglia. Treating with steroids was usually associated with a rapid recovery and both intravenous high dose methylprednisolone and dexamethasone had the same effect. All patients survived. Twenty three patients recovered completely with only mild sequelae in the remaining five children.
Keywords: acute; disseminated; encephalomyelitis; children